Fenomena Job Hopping: Persepsi Dukungan Atasan, Komitmen Organisasi, dan Retensi Karyawan pada Karyawan Gen Z - Claristia, Agnes; Etikariena, Arum (INSAN Jurnal Psikologi dan Kesehatan Mental, 2024)
Nowadays, job hopping among Gen Z poses a challenge for companies in retaining employees. This study aims to analyze the influence of perceived supervisor support on employee retention, with organizational commitment as a moderating variable. The data obtained from 186 Gen Z participants were processed using moderation analysis using JAMOVI 2.3.28. The results showed that perceived supervisor support positively influenced employee retention. Furthermore, organizational commitment was found to strengthen the effect of perceived supervisor support on retention, especially when organizational commitment was at a low level. The role of supervisors is crucial in supporting employee development, and companies need to build strong organizational commitment to enhance employee loyalty. These findings can serve as a guide for companies in developing employee retention strategies, particularly in addressing the job hopping phenomenon among Gen Z.